KEANEKARAGAMAN HAYATI VEGETASI PADA PRAKTIK AGROFORESTRIDAN KAITANNYA TERHADAP FUNGSI EKOSISTEM DI TAMAN NASIONAL MERU BETIRI, JAWA TIMUR - Adisti Permatasari Putri Hartoyo; Nurheni Wijayanto; TA Karimatunnisa; AN Ikhfan (Lambung Mangkurat University-Indonesia, 2019)
The local communities in rehabilitation zone of Meru Betiri National Park (TNMB) play important role to maintain ecosystem functions. However, baseline data regarding vegetation biodiversity and their associated ecosystem functions in rehabilitation zone of TNMB is still lacking and needs further research in achieving sustainable forest management. The objective of this research was to study the vegetation biodiversity in agroforestry practice and their associated ecosystem functions in TNMB, East Java. This research used purposive sampling and vegetation analysismethods. Based on canopy density, the research sites were categorized into dense (class 1), moderate (class 2), and low (class 3). The result showed that as habitat function, agroforestry practice in TNMB had the highest number of individual at seedling, sapling, pole and tree in class 3 (1130 ind/ha), class 1 (271 ind/ha), class 1 (338 ind/ha), and class 2 (88 ind/ha) respectively. Based on diversity (H’) and Margalef (Dmg) indices, all research plots and level growth were categorized into low category. At tree, pole, and sapling levels were dominated by banana (Musa sp.), while at seedling level in class 1, 2, and 3 were dominated by kacang asu (Calopogium mucunoides), rumput Melinis (Melinis minutiiflora), and rumput malela (Brachiaria mutica) respectively. As regulation function, soil quality in this location was infertile. Therefore, land cultivation and enrichment planting are necessary not only to increase the number of soil organic matter, but also to increase H’ and Dmg by planting local species trees (e.g D. zibethinus, A. muricata, A. heterophyllus, and P. timoriana).